Absorptive capacity in family firms: a systematic literature review - Laura Pütz; Arndt Werner (Review of Managerial Science, 2023)
Two-thirds of all businesses worldwide are family firms. For these family firms, absorptive capacity (AC) is key to acquiring, assimilating, transforming, and exploiting new, external knowledge for purposes of value creation. In this study, we conduct a literature review to obtain an overview of the existing research on AC in family firms. Drawing on 27 articles, we show that because of the family members' induced influence on the family firm, the findings from previous studies based on non-family businesses cannot be applied to family businesses. In fact, we demonstrate that this influence can even create ambiguous effects on the integration of AC into the firm. The results of our literature review indicate that on the one hand, family members promote the integration of external knowledge, that is, they utilize their family-specific resources. On the other hand, tapping on such family-specific resources can simultaneously cause family firms to isolate themselves and restrict the firm's access to external knowledge. Our analysis also reveals that research on AC in family firms is mostly conducted on a conceptual level and that the few empirical studies usually draw on simple, one-dimensional constructs. Thus, we encourage more future empirical research to draw on the multidimensional constructs of AC and family influence.
Keywords: M1; L2; D8; 650; Systematic literature review; Family business; Absorptive capacity; Heterogeneity